2015
DOI: 10.1080/15313204.2014.991983
|View full text |Cite
|
Sign up to set email alerts
|

Solution-Focused Brief Therapy in China: A Meta-Analysis

Abstract: The primary aim of this study was to assess the overall effectiveness of solution-focused brief therapy (SFBT) among Chinese populations with mental and behavioral health issues. A random effects meta-analysis of nine eligible studies was conducted on SFBT outcomes in China. SFBT was effective in reducing internalizing problems, with effect sizes ranging from g = 0.49 to 3.22. Results from pooled effect size estimates favoring SFBT ( g = 1.26) were large. These results highlight the positive impact SFBT has on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 23 publications
0
23
0
2
Order By: Relevance
“…Similarly, international domicile produced twice the treatment effect when compared to domiciles in the United States. For example, in a meta-analysis conducted by Kim et al (2015), SFBT was found to be moderately effective with decreasing internalizing disorders in Chinese clients. In some cultures, receiving mental health services may be considered taboo, thus individuals who sought treatment may have done so with a larger degree of motivation, which may explain the notable dissimilarities in treatment effects.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, international domicile produced twice the treatment effect when compared to domiciles in the United States. For example, in a meta-analysis conducted by Kim et al (2015), SFBT was found to be moderately effective with decreasing internalizing disorders in Chinese clients. In some cultures, receiving mental health services may be considered taboo, thus individuals who sought treatment may have done so with a larger degree of motivation, which may explain the notable dissimilarities in treatment effects.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a study by Motsoaledi and Cilliers (2012), executives gained insights and an increased self-awareness of diversity within their organizations through their participation in a coaching program that was based on a problem-focused approach. Research examining the solution-focused approach provides evidence of its effectiveness in a broad range of settings (e.g., in clinical, organizational, and educational settings; Gingerich & Peterson, 2013;Theeboom et al, 2014) for achieving positive change in a wide variety of populations (Gingerich & Peterson, 2013;Kim et al, 2015;Sezer, 2017). However, some studies have indicated that when training approach was similar, some participants benefited more than others from coaching intervention (Campbell, 1988;Tannenbaum & Yukl, 1992).…”
Section: Coaching Approach As a Moderator In The Association Between mentioning
confidence: 99%
“…Researchers have noted that the specific questioning techniques (e.g., miracle questions, scaling, etc.) are an important means of facilitating changes with clients (e.g., Beyebach, ), and that increasing positive expectancies, and positive emotion, such as hope and optimism, may be associated with positive outcomes within SFBT (e.g., Kim & Franklin, ; Kiser, Piercy, & Lipchik, ; Lipchik, ).…”
Section: Solution‐focused Brief Therapymentioning
confidence: 99%